The proteome of cblC defect: in vivo elucidation of altered cellular pathways in humans. Issue 5 (14th January 2015) - Caterino, Marianna; Pastore, Anna; Strozziero, Maria Grazia; Di Giovamberardino, Gianna; Imperlini, Esther; Scolamiero, Emanuela; Ingenito, Laura; Boenzi, Sara; Ceravolo, Ferdinando; Martinelli, Diego; Dionisi‐Vici, Carlo; Ruoppolo, Margherita
Abstract: Methylmalonic acidemia with homocystinuria, cobalamin deficiency type C (cblC) (MMACHC) is the most common inborn error of cobalamin metabolism. Despite a multidrug treatment, the long‐term follow‐up of early‐onset patients is often unsatisfactory, with progression of neurological and ocular impairment. Here, the in‐vivo proteome of control and MMACHC lymphocytes (obtained from patients under standard treatment with OHCbl, betaine, folate and L‐carnitine) was quantitatively examined by two dimensional differential in‐gel electrophoresis (2D‐DIGE) and mass spectrometry. Twenty three proteins were found up‐regulated and 38 proteins were down‐regulated. Consistent with in vivo studies showing disturbance of glutathione metabolism, a deregulation in proteins involved in cellular detoxification, especially in glutathione metabolism was found. In addition, relevant changes were observed in the expression levels of proteins involved in intracellular trafficking and protein folding, energy metabolism, cytoskeleton organization and assembly. This study demonstrates relevant changes in the proteome profile of circulating lymphocytes isolated from treated cblC patients. Some results confirm previous observations in vivo on fibroblast, thus concluding that some dysregulation is ubiquitous. On the other hand, new findings could be tissue‐specific. These observations expand our current understanding of the cblC disease and may ignite new research and therapeutic strategies to treat this disorder.